Analysis of Different Treatment Methods for Autism - Peng, Zisu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Autism, the full name of autism spectrum disorder, is a type of inborn, congenital, or onset in infancy, characterized by social communication difficulties, narrow interests, repetitive stereotyped behaviors, and sensory perception. In recent decades, the incidence of autism has been increasing worldwide. It is estimated that the average prevalence of autism worldwide is about 1%. Therefore, there is no doubt that autism has become a public health issue that has attracted great attention and attention from societies and governments around the world. It is also one of the key topics in neuro-medical research today, although many researchers have conducted corresponding clinical experiments on treatments for autism. However, there are still some unresolved problems in the treatment of autism in Chinese medicine. As a result, this article uses literature review and survey research methods, mainly studies and summarizes traditional Chinese and Western medicine in the treatment of autism and compares the shortcomings of traditional Chinese medicine in the treatment of patients with autism. And the treatment and popularization of autism still need to continue to be researched and promoted.